Investigating a Class of Nonlinear Fractional Differential Equations and Its Hyers-Ulam Stability by Means of Topological Degree Theory. (10th September 2019) - Shah, Kamal; Hussain, Wajid
Abstract: The aim of this article is to seek some adequate conditions via a prior estimate method (topological degree method) to derive the existence of solution to a nonlinear boundary value problem of fractional differential equations (FDEs). With the help of topological degree method which has been applied in many articles, we establish the required results for existence and uniqueness of solution to a class of FDEs. Moreover, we also formulate sufficient conditions for Hyers-Ulam stability to the solution of the considered problem. Finally, an appropriate example is provided to justify the relevant results.